# How do you simplify #6--10+ -4#?

6 + 10 - 4 = 12

By the rules of negatives and positives in math, two negatives makes a positive, so 6 - - 10 = 6 + 10. However, a positive and a negative makes a negative, so 10 + - 4 = 10 - 4.

This makes the resulting equation 6 + 10 - 4. By PEMDAS, it does not matter which you do first (addition and subtraction are 'equally important'), so going from left to right, 6 + 10 - 4 = 16 - 4 = 12.

By signing up, you agree to our Terms of Service and Privacy Policy

To simplify 6--10+ -4, you first remove the double negative: 6 - (-10) - 4 = 6 + 10 - 4

Then, you perform addition and subtraction from left to right: 6 + 10 - 4 = 16 - 4

Finally, you subtract: 16 - 4 = 12

Therefore, 6--10+ -4 simplifies to 12.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7